In Search of a Silver Bullet: Child Welfare's Embrace of Predictive Analytics. (March 2017) - Church, Christopher E.; Fairchild, Amanda J.
Abstract: Predictive analytics has shaken up a number of fields, including child welfare. Predictive analytics refers to the process of applying statistical algorithms to data to make informed guesses about future events. Although predictive analytics can help professionals make decisions more accurately, objectively, and quickly, there is a concern that some methods may result in discriminatory practices or consequences for vulnerable children and families. This paper examines a number of programmatic and ethical considerations for determining the appropriate role of predictive analytics in child welfare.